Changes in Quality of Life Among Enrollees in Hennepin Health: A Medicaid Expansion ACO. (February 2020) - Vickery, Katherine D.; Shippee, Nathan D.; Guzman-Corrales, Laura M.; Cain, Cindy; Turcotte Manser, Sarah; Walton, Tom; Richards, Jessica; Linzer, Mark
Despite limited program evaluations of Medicaid accountable care organizations (ACOs), no studies have examined if cost-saving goals negatively affect quality of life and health care experiences of low-income enrollees. The Hennepin Health ACO uses an integrated care model to address the physical, behavioral, and social needs of Medicaid expansion enrollees. As part of a larger evaluation, we conducted semistructured interviews with 35 primary care using Hennepin Health members enrolled for 2 or more years. Using fuzzy set qualitative comparative analysis, we assessed enrollee complexity and use of the care model and improvements in quality of life. We found improved quality of life was consistently associated with strong bonds to primary care, consistent mental health care, and support from extended care team members. Comprehensive, integrated care models within ACOs may improve quality of life for low-income Medicaid enrollees through coordinated primary and mental health care.